2015
DOI: 10.1016/j.jagp.2014.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Circadian Rest–Activity Rhythms Predict Future Increases in Depressive Symptoms Among Community-Dwelling Older Men

Abstract: Objectives Circadian rest-activity rhythms (CARs) have been cross-sectionally associated with depressive symptoms, however no longitudinal research has examined whether CARs are a risk factor for developing depressive symptoms. Methods We examined associations of CARs (measured with actigraphy over a mean of 4.8 days) with depressive symptoms (measured with the Geriatric Depression Scale) among 2892 community-dwelling older men (mean age: 76.2 +/− 5.5) from the MrOS Sleep Study who were without cognitive imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
52
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 38 publications
4
52
0
Order By: Relevance
“…Note that this finding is consistent with our prior study which found that an association between low rhythm amplitude and future depression was accounted for by concurrent health status covariates (Smagula, Ancoli-Israel et al, 2014b). The present work also found that all three sub-groups with indication of more delayed activity rhythms experienced significantly faster increases in depressive symptoms over time, independent of including chronic diseases, night-time sleep characteristics, and self-reported physical activity; when later activity timing was accompanied by either a compressed active period or low activity levels, depressive symptom increases appeared somewhat faster (compared with having later activity timing alone).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Note that this finding is consistent with our prior study which found that an association between low rhythm amplitude and future depression was accounted for by concurrent health status covariates (Smagula, Ancoli-Israel et al, 2014b). The present work also found that all three sub-groups with indication of more delayed activity rhythms experienced significantly faster increases in depressive symptoms over time, independent of including chronic diseases, night-time sleep characteristics, and self-reported physical activity; when later activity timing was accompanied by either a compressed active period or low activity levels, depressive symptom increases appeared somewhat faster (compared with having later activity timing alone).…”
Section: Discussionsupporting
confidence: 92%
“…For timing parameters, the lowest and the highest quartiles were both compared with the others (in a single variable) to represent both phase advances and delays. Using quartiles to represent non-normative or disturbed activity rhythm parameters is consistent with prior work (Paudel, Taylor et al, 2010; Tranah, Blackwell et al, 2010; Tranah, Blackwell et al, 2011; Smagula, Ancoli-Israel et al, 2014b) and, in the context of LCA, is designed to identify subgroups with specific patterns of activity rhythm parameters outside the normative range (disturbances).…”
Section: Methodsmentioning
confidence: 76%
See 2 more Smart Citations
“…Standardized amplitude and having a later-up mesor were also associated with depression symptoms, but these associations were attenuated by adjustments for covariates. Consistent with these findings, my colleagues and I recently found that community-dwelling older men with low standardized amplitude (indicating a dampened RAR) were more likely to have prevalent depression symptoms, but that this association was completely attenuated after adjusting for concurrent health status measures (7). Later RAR timing (up-mesor and acrophase) was also associated with the presence of depression symptoms, but again, these associations could be explained by adjustments for health status covariates.…”
Section: Evidence For Rars As a Marker Of Depressionmentioning
confidence: 63%